Terrorismo e direitos humanos: análise da possibilidade de controle judicial das resoluções do CSONU - Costa, Joabe Alves da (Universidade Federal Rural do Semi-Árido, 2017)
The debate about the need and the best way to combat terrorism is convincing. All normative developments have been moving towards compliance with the most effective solution against terrorism, but it faces certain obstacles. Among them, the complexity of the phenomenon and the difficulty of the fight against it stand out in this work, to question whether the repressive norms, especially the Security Council, have been based on a coherent perspective of protection of human rights in the fight against The terrorism The issue is relevant since it increases the development of restrictive resolutions of fundamental freedoms on the part of the Security Council and states as Brazil does not foresee the necessity of its internalization throught pass the scrutiny of the legislative branch, besides recurring violations in the body of these resolutions. The research follows the deductive method and makes use of literature and international jurisprudence. Terrorism will now be exposed on the international scene and its regulatory development within the UN; The procedure for incorporating Security Council resolutions into Brazilian legislation will then be analyzed and demonstrate the existence of UNSC resolutions that contain violations of human rights / fundamental rights In the end, will discuss the control of a determination of this organ manufactured in the regional system of the EU. It is possible to conclude that counter-terrorism strategies in the UN are not compatible with the protection of human rights in all cases, since, in some situations, hegemonic measures proclaimed by international organizations may be more detrimental to Human rights of persons than the provisions and practices of internal or regional orders. This makes it necessary for the continuation of dialogue between such regulatory and judicial structures, as measures to combat terror and the protection of human rights must go hand in hand, being complementary, where both mutually reinforce each other.
Artigo Acadêmico
Keywords: Terrorismo; Direitos humanos; Controle judicial; Terrorism; Human rights; Judicial control; CIENCIAS SOCIAIS APLICADAS::DIREITO